A method for preparing sodium ferrous sulfate positive electrode material for sodium ion battery and vehicle
By building a three-dimensional conductive carbon network and dense protective film in the positive electrode material of sodium ion battery, the poor conductivity and air stability of the iron-based sulfate positive electrode material are solved, and high capacity, fast charging performance and stability are improved.
Patent Information
- Application Number
- CN202411442794.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The intrinsic electronic conductivity of the iron-based sulfate cathode material has poor intrinsic electronic conductivity, resulting in unsatisfactory rate performance, and the material is easily soluble in water and easily oxidized by air, making it impossible to obtain ultra-high fast charging performance, and no significant improvement in air stability.
By mixing anhydrous ferrous sulfate, sodium sulfate, carbon source and aluminum source, the precursor material is obtained and annealed under the protection of inert gas to build a three-dimensional conductive carbon network and a dense protective film to improve the air of the positive electrode material Stability and conductivity.
The high capacity, air stability and conductivity of sodium ferrous sulfate cathode material has been improved, and the fast charging performance and cycle life of sodium ion batteries have been improved.
Smart Images

Figure CN118954614B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of synthesis of positive electrode materials for sodium ion batteries, and specifically relates to a preparation method and a vehicle of sodium ferrous sulfate positive electrode materials for sodium ion batteries. Background Art
[0002] Typical positive electrode materials for sodium-ion batteries include layered transition metal oxides, polyanionic compounds, Prussian blue analogs, and organic materials. In contrast, polyanionic compounds have the advantages of excellent stability, high redox potential, and high safety, making them potential high-performance positive electrode materials. Among the many polyanionic compounds, iron-based sulfates have a higher operating voltage and thus a higher energy density due to the stronger electronegativity of the sulfate group. Among them, sodium ferrous sulfate (Na x Fe y (SO 4 ) z ), which not only has high theoretical capacity and high operating voltage, but also has abundant raw material reserves and is considered to be a promising positive electrode material for sodium-ion batteries.
[0003] However, the intrinsic electronic conductivity of iron-based sulfate cathode materials is poor, which is not conducive to the conduction of electrons inside, resulting in unsatisfactory rate performance, which in turn limits practical applications. At the same time, iron-based sulfate cathode materials are highly soluble in water and easily oxidized by air. In addition, ultra-high fast charging performance cannot be obtained through current conventional synthesis or modification methods, and there is no significant improvement in the air stability of sodium ferrous sulfate cathode materials.
[0004] Therefore, the development of a low-cost, environmentally friendly, fast-charging, and air-stable iron-based sulfate polyanion cathode material meets the urgent needs of the current development of sodium-ion batteries. Summary of the invention
[0005] The object of the present invention is to provide a method for preparing a sodium ferrous sulfate positive electrode material for a sodium ion battery and a vehicle. The obtained positive electrode material has no impurities and has a high capacity, and can improve the air stability and conductivity of the sodium ferrous sulfate positive electrode material.
[0006] The technical solution adopted by the present invention to achieve the above-mentioned purpose is:
[0007] A method for preparing a sodium ferrous sulfate positive electrode material for a sodium ion battery comprises:
[0008] Anhydrous ferrous sulfate, sodium sulfate, a carbon source and an aluminum source are mixed and ground to obtain a precursor material; the precursor material is heated and annealed under the protection of an inert gas to obtain a sintered product; the sintered product is cooled to room temperature and ground to obtain a sodium ferrous sulfate positive electrode material; the carbon source includes one or more of reduced graphene oxide, acetylene black, Ketjen black, conductive graphite, carbon nanotubes (CNTs) and modified carbon nanotubes; the modified carbon nanotubes contain nitrogen, and the nitrogen comes from methotrexate and / or 2-aminopyrimidine.
[0009] Furthermore, the aluminum source includes one or more of aluminum isopropoxide, aluminum oxide, aluminum acetate, aluminum chloride, aluminum sulfate, aluminum nitrate, aluminum oxalate and aluminum acetate.
[0010] Furthermore, the molar ratio of anhydrous ferrous sulfate to sodium sulfate is 1-2:1;
[0011] The amount of carbon source is 1-5wt% of the sum of anhydrous ferrous sulfate and sodium sulfate; the amount of aluminum source is 1-5wt% of the sum of anhydrous ferrous sulfate and sodium sulfate.
[0012] According to one aspect of the present invention, the modified carbon nanotubes are prepared by reacting a mixed nitrogen source with oxidized carbon nanotubes; the mixed nitrogen source includes methotrexate and 2-aminopyrimidine; and the oxidized carbon nanotubes are obtained by oxidation of CNTs.
[0013] Adding an appropriate amount of modified carbon nanotubes with a bamboo-like structure in the preparation of positive electrode materials can significantly improve the electrochemical performance of sodium ion batteries. This may be because the addition of elements such as oxygen, nitrogen, and sulfur in the modified carbon nanotubes changes their electronegativity, thereby enhancing the electron transfer rate during the charge and discharge process, which helps the transfer of sodium ions in the electrolyte; and the spatial structure of the modified carbon nanotubes changes, which increases the electrochemical active area in the positive electrode material, which also helps the embedding and extraction of sodium ions.
[0014] Preferably, in the preparation of the modified carbon nanotubes, the weight ratio of the oxidized carbon nanotubes to the mixed nitrogen source is 1:10-20; in the mixed nitrogen source, the weight ratio of methotrexate to 2-aminopyrimidine is 1:4-12.
[0015] Preferably, in the preparation of the modified carbon nanotubes, the nitrogen source is mixed with the oxidized carbon nanotubes and then mixed with the sulfur source; the weight ratio of the sulfur source to the oxidized carbon nanotubes is 1:10-18.
[0016] Specifically, a method for preparing a sodium ferrous sulfate positive electrode material for a sodium ion battery comprises the following steps:
[0017] Step 1: preparing anhydrous ferrous sulfate;
[0018] Step 2: Mix anhydrous ferrous sulfate, sodium sulfate, a carbon source and an aluminum source and grind them;
[0019] Step 3: After adding anhydrous ethanol to the mixed raw materials, grinding is carried out under the protection of inert gas to obtain a precursor material;
[0020] Step 4: heating the precursor material obtained in step 3, and annealing it under the protection of an inert gas to obtain a sintered product;
[0021] Step 5: Cool the sintered product obtained in step 4 to room temperature, and grind it to obtain the sodium ferrous sulfate positive electrode material.
[0022] Furthermore, in step 1, ferrous sulfate heptahydrate is dehydrated in a tube furnace at 200-300° C. for 3-12 h under the protection of an inert gas to obtain anhydrous ferrous sulfate, wherein the inert gas is one of nitrogen, argon, helium, etc.
[0023] Furthermore, in step 2, the molar ratio of anhydrous ferrous sulfate to sodium sulfate is 1-2:1.
[0024] Preferably, in step 2, the carbon source includes one or more of reduced graphene oxide, acetylene black, Ketjen black, conductive graphite, carbon nanotubes and modified carbon nanotubes; the aluminum source includes one or more of aluminum isopropoxide, aluminum oxide, aluminum acetate, aluminum chloride, aluminum sulfate, aluminum nitrate, aluminum oxalate and aluminum acetate.
[0025] Furthermore, in step 2, the amount of carbon source used is 1-5 wt % of the sum of anhydrous ferrous sulfate and sodium sulfate used.
[0026] Furthermore, in step 2, the amount of aluminum source used is 1-5wt% of the sum of anhydrous ferrous sulfate and sodium sulfate used.
[0027] Furthermore, in step 2, the carbon source is reduced graphene oxide and acetylene black, and the weight ratio of the two is 1-3:1; or, the carbon source is graphene and carbon nanotubes, and the weight ratio of the two is 1-3:1; or, the carbon source is acetylene black and modified carbon nanotubes, and the weight ratio of the two is 1-3:1; or, the carbon source is graphene and acetylene black, and the weight ratio of the two is 1-3:1; or, the carbon source is Ketjen black, conductive graphite, and carbon nanotubes, and the weight ratio of the three is 1:1-3:1-3.
[0028] Furthermore, in step 2, the aluminum source is aluminum isopropoxide and aluminum oxide, and the weight ratio of the two is 1-3:1; or, the aluminum source is aluminum acetate and aluminum chloride, and the weight ratio of the two is 1-3:1; or, the aluminum source is aluminum sulfate, aluminum nitrate, and aluminum oxalate, and the weight ratio of the three is 1:1-3:1-3.
[0029] Preferably, before step 3, zirconium oxide beads are added to the ground material, and the total mass of the zirconium oxide beads is 30-60: 1 to the material mass ratio. Zirconia beads with diameters of 3 mm, 5 mm and 10 mm are selected and mixed for use, and the mass ratio of the above three diameters of zirconium oxide beads is 2:1:1.
[0030] Furthermore, in step 3, the inert gas is nitrogen or argon, and the grinding is performed by wet ball milling, the rotation speed of the wet ball milling is 200-800 rpm, and the ball milling time is 2-12 h;
[0031] In step 4, the inert gas is nitrogen or argon, the heating rate of the heating treatment is 2-20 °C / min, the annealing temperature is 300-450 °C, and the annealing time is 6-36 h.
[0032] By adopting the above technical scheme, the sulfate positive electrode material is in situ coated with a carbon source and an aluminum source to achieve the construction of a three-dimensional conductive carbon network and a dense protective film, thereby improving the air stability of the resulting sodium ion battery and optimizing the battery's fast charging performance and cycle life.
[0033] According to one aspect of the present invention, a sodium ferrous sulfate positive electrode material for a sodium ion battery is provided, which is prepared by the above method.
[0034] According to one aspect of the present invention, there is provided a method for preparing a positive electrode sheet for a sodium ion battery, comprising:
[0035] Anhydrous ferrous sulfate, sodium sulfate, a carbon source and an aluminum source are mixed and ground to obtain a precursor material; the precursor material is heated and annealed under the protection of an inert gas to obtain a sintered product; the sintered product is cooled to room temperature and ground to obtain a sodium ferrous sulfate positive electrode material; the sodium ferrous sulfate positive electrode material is coated on a positive electrode current collector to obtain a sodium ion battery positive electrode sheet. The carbon source includes one or more of reduced graphene oxide, acetylene black, Ketjen black, conductive graphite, carbon nanotubes and modified carbon nanotubes; the modified carbon nanotubes contain nitrogen, and the nitrogen comes from methotrexate and / or 2-aminopyrimidine.
[0036] Preferably, the molar ratio of anhydrous ferrous sulfate to sodium sulfate is 1-2:1; the amount of carbon source is 1-5wt% of the sum of anhydrous ferrous sulfate and sodium sulfate; the amount of aluminum source is 1-5wt% of the sum of anhydrous ferrous sulfate and sodium sulfate.
[0037] According to one embodiment of the present invention, the carbon source includes modified carbon nanotubes and one or more of reduced graphene oxide, acetylene black, Ketjen black, conductive graphite and carbon nanotubes.
[0038] According to one embodiment of the present invention, the modified carbon nanotubes are prepared by reacting a mixed nitrogen source with oxidized carbon nanotubes; the mixed nitrogen source includes methotrexate and 2-aminopyrimidine; and the oxidized carbon nanotubes are obtained by oxidation of CNTs.
[0039] The use of modified carbon nanotubes in combination with other carbon sources as a composite carbon source is beneficial to the conduction of electrons in iron-based sulfate positive electrode materials, thereby improving the rate performance. The spatial structure of the modified carbon nanotubes is more complex, has a higher capacity, and helps to promote the diffusion of sodium ions in the electrolyte. This may be because the use of methotrexate and / or 2-aminopyrimidine as a nitrogen source changes the spatial structure of CNTs during the treatment of CNTs, and the resulting modified carbon nanotubes have a partitioned, bamboo-like structure. The bamboo-like structure of the modified carbon nanotubes has a positive effect on the performance improvement of sodium ion batteries and also helps to improve the structural stability of the positive electrode sheet. Methotrexate and 2-aminopyrimidine as a mixed nitrogen source may help to improve the regularity of the segmented structure of the modified carbon nanotubes, thereby making the sodium ions in the resulting positive electrode material more evenly distributed, which is beneficial to the transfer of sodium ions during the charge and discharge process.
[0040] According to one aspect of the present invention, a method for preparing modified carbon nanotubes comprises the following steps:
[0041] Step 1: treating CNTs by potassium permanganate oxidation method to obtain oxidized carbon nanotubes;
[0042] Step 2: Methotrexate and 2-aminopyrimidine are used as a mixed nitrogen source, mixed with the oxidized carbon nanotubes obtained in step 1, and nitrogen-doped carbon nanotubes (CNTs-N) are synthesized by high-temperature pyrolysis.
[0043] Preferably, step 1 includes the following steps:
[0044] S1.1 Add 0.5 mol / L H 2 SO 4 After ultrasonic treatment for 20-30 min, CNTs / H 2 SO 4 Mixed solution; CNTs and H 2 SO 4 The mass volume ratio is: 1g:200-300mL.
[0045] S1.2 KMnO 4 Dissolved in 0.5 mol / L H 2 SO 4 In the experiment, KMnO was obtained. 4 / H 2 SO 4 Mixed solution, in which KMnO 4 With H2 SO 4 The mass volume ratio is: 2.5g:200-300mL.
[0046] S1.3 At 120-160℃, the KMnO 4 / H 2 SO 4 The mixture was slowly added with CNTs / H 2 SO 4 The mixed solution was refluxed for 5-7 hours, cooled to room temperature, filtered to obtain a filter cake, and the obtained filter cake was added to concentrated HCl, mixed and allowed to stand for a period of time to remove the MnO generated in the reaction. 2 The mixture was then filtered and washed with water until the filtrate was neutral. The filter cake was vacuum dried at 70-85°C for 10-15h to obtain oxidized carbon nanotubes.
[0047] Preferably, in step 2, the weight ratio of methotrexate to 2-aminopyrimidine is 1:4-12.
[0048] Preferably, step 2 comprises the following steps:
[0049] S2.1 adding a mixed nitrogen source to the oxidized carbon nanotubes obtained in step 1, wherein the weight ratio of the mixed nitrogen source to the oxidized carbon nanotubes is 1:10-18; grinding for 30-60 minutes to mix the materials evenly;
[0050] S2.2 The mixture obtained in S2.1 is treated at high temperature in a nitrogen atmosphere, with a heating rate of 5-10°C / min to 700-800°C, and the temperature is maintained for 0.5-1.5h, and then cooled to room temperature to obtain CNTs-N.
[0051] Furthermore, in step 2, the mixed nitrogen source is mixed with the oxidized carbon nanotubes obtained in step 1, and then mixed with a sulfur source, and then high-temperature pyrolysis is used to synthesize sulfur-doped carbon nanotubes.
[0052] Preferably, the weight ratio of the sulfur source to the oxidized carbon nanotubes is 1:10-18.
[0053] Preferably, the sulfur source is a mixed sulfur source, and the mixed sulfur source includes cystine and 4-azidophenyl disulfide. Further, in the mixed sulfur source, the weight ratio of cystine to 4-azidophenyl disulfide is 1:1-3.
[0054] Therefore, the addition of sulfur source can further improve the performance of sodium ion battery, improve the first effect of ion battery, and positive electrode energy density. This may be because the addition of sulfur source, especially the addition of cystine and 4-azidophenyl disulfide as mixed sulfur source, makes CNTs doped with sulfur after modification. The addition of sulfur further changes the spatial structure of modified carbon nanotubes, and its bamboo-like structure is more diversified; the use of cystine and 4-azidophenyl disulfide makes the spatial structure of the modified carbon nanotubes more complex, and the paths of sodium ions in the process of embedding and embedding are diversified, which helps to promote the diffusion of sodium ions in the electrolyte. And the presence of nitrogen and sulfur elements changes the electronegativity of the modified carbon nanotubes, which helps the transfer of sodium ions during the charge and discharge process. Thereby affecting the electrochemical performance of the obtained sodium ion battery.
[0055] According to one aspect of the present invention, a sodium ion battery positive electrode plate is provided, comprising a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, the positive electrode film layer comprising a sodium ferrous sulfate positive electrode material obtained by the above-mentioned method for preparing a sodium ferrous sulfate positive electrode material for a sodium ion battery.
[0056] According to one aspect of the present invention, there is provided an application of the above-mentioned sodium ferrous sulfate positive electrode material in a sodium ion half-cell, using metallic sodium as a counter electrode.
[0057] According to one aspect of the present invention, there is provided a sodium ion battery comprising the above-mentioned positive electrode plate.
[0058] According to one aspect of the present invention, there is provided a vehicle, comprising the above-mentioned sodium ion battery; the vehicle includes but is not limited to an electric car, an electric bicycle, an electric forklift, and an electric scooter.
[0059] Compared with the prior art, the present invention has the following beneficial effects:
[0060] (1) By adjusting the molar ratio of sulfates, a sodium ferrous sulfate cathode material with no impurities and high capacity was obtained;
[0061] (2) Through the application of composite carbon source and composite aluminum source, the in-situ coating of sulfate cathode materials is achieved, and a three-dimensional conductive network and a dense protective film are simultaneously constructed on the surface of sodium ferrous sulfate cathode materials, thereby improving the air stability and conductivity of sodium ferrous sulfate cathode materials to obtain good fast charging performance and stability;
[0062] (3) The raw materials of the present invention are cheap and readily available, the preparation method is simple, the process flow is pollution-free, and it is easy to realize industrial continuous production; and the preparation method of the sodium iron sulfate positive electrode material of the present invention is simple, with low energy consumption and high yield, and is suitable for large-scale production;
[0063] (4) The use of modified carbon nanotubes makes the positive electrode material have higher ion conductivity and positive electrode energy density, making the structure of the positive electrode sheet more stable, which can significantly improve the battery performance of sodium ion batteries. This may be because the modified carbon nanotubes have a bamboo-like structure that increases the electrochemical active area in the positive electrode material, which is conducive to the embedding and extraction of sodium ions; in addition, the addition of elements such as oxygen, nitrogen, and sulfur in the modified carbon nanotubes changes its electronegativity, thereby enhancing the electron transfer rate during the charge and discharge process, which also helps the transfer of sodium ions in the electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Figure 1 This is the XRD diagram of the sodium ferrous sulfate positive electrode material for sodium ion battery in Example 1 of the present invention;
[0065] Figure 2 This is a SEM image of the sodium ferrous sulfate positive electrode material for sodium ion battery in Example 1 of the present invention;
[0066] Figure 3 XRD comparison diagram of the sodium ferrous sulfate positive electrode material for sodium ion battery in Example 1 of the present invention exposed to air for 0 days, 14 days and 30 days;
[0067] Figure 4 The charge and discharge curves of the battery obtained in Example 1 of the present invention at different current densities;
[0068] Figure 5 TEM image of CNTs-N of Example 3 of the present invention;
[0069] Figure 6 This is a TEM image of CNTs-N of Example 3 of the present invention. DETAILED DESCRIPTION
[0070] The technical solution of the present invention is further described in detail below in conjunction with specific implementation methods and drawings. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0071] Example 1
[0072] Preparation of sodium ferrous sulfate positive electrode material for sodium ion batteries
[0073] Step 1: preparing anhydrous ferrous sulfate; removing water from ferrous sulfate heptahydrate in a tube furnace at 300° C. for 4 h under a nitrogen atmosphere to obtain anhydrous ferrous sulfate.
[0074] Step 2: Mix the anhydrous ferrous sulfate obtained in step 1 with sodium sulfate, a carbon source and an aluminum source and grind them, wherein the molar ratio of anhydrous ferrous sulfate to sodium sulfate is 1:1; the carbon source includes graphene and carbon nanotubes (CNTs), and the weight ratio of the two is 1:1; the aluminum source includes aluminum isopropoxide and aluminum oxide, and the weight ratio of the two is 1:1; the weight ratio of the mixture of anhydrous ferrous sulfate and sodium sulfate to the carbon source and the aluminum source is 95:3:2.
[0075] Zirconia beads are added to the mixed and ground material, and the ratio of the total mass of the zirconia beads to the mass of the material is 30:1; and zirconia beads with diameters of 3 mm, 5 mm and 10 mm are mixed and used, and the mass ratio of the above three diameters of zirconia beads is 2:1:1.
[0076] Step 3: Add anhydrous ethanol to the mixed materials, and immerse all the powdered materials in anhydrous ethanol, and then perform wet ball milling under argon protection to obtain the precursor material. The wet ball milling speed is 800 rpm and the ball milling time is 3 h.
[0077] Step 4: Heat the precursor material obtained in step 3 and perform annealing under nitrogen protection. The heating rate of the heating treatment is 5°C / min; the annealing temperature is 400°C, and the annealing time is 12 h to obtain a sintered product.
[0078] Step 5: The sintered product obtained in step 4 is cooled to room temperature and then manually ground for 10 minutes until no large particles are visible to the naked eye, thereby obtaining the sodium ferrous sulfate positive electrode material Na 6 Fe 4 (SD 4 ) 7 .
[0079] The XRD pattern of the positive electrode material obtained according to the above steps is shown in Figure 1 ; SEM images see Figure 2 In addition, the cathode material obtained in the above steps was exposed to air, and the fresh cathode material and the cathode material exposed to air for 14 days and 30 days were tested, and the obtained XRD patterns were shown in Figure 3 .
[0080] Preparation of sodium ion batteries
[0081] 1. Preparation of positive electrode
[0082] The sodium ferrous sulfate positive electrode material, acetylene black and N-methylpyrrolidone / polyvinylidene fluoride (5wt%) obtained above were mixed in a mass ratio of 95:3:2, and the obtained mixture was manually ground with a mortar for 10 minutes to make it evenly mixed, and then transferred to an oscillation tube, and a few zirconium dioxide beads with a diameter of 3mm were added. The mixture was oscillated and ground with a micro-vibration ball mill. The oscillation frequency was set to 3000rpm and the mixture was oscillated for 15 minutes to obtain a mixed slurry. The obtained mixed slurry was coated on aluminum foil and placed in a vacuum drying oven at 80°C for vacuum drying for 6 hours to completely evaporate the solvent N-methylpyrrolidone in the binder, and then cut into pieces to obtain positive electrode sheets.
[0083] 2. Preparation of sodium ion batteries
[0084] The hard carbon negative electrode sheet and PP separator are used together with the positive electrode sheet obtained above, and the dry cells are assembled in a stacking manner, and then encapsulated with aluminum plastic film, and the electrolyte is injected, and then the formation is waited. The formation upper limit voltage is controlled to 4.0-4.5V. The obtained cells are further assembled into batteries.
[0085] All battery assemblies were performed in a glove box (0 wt% ≤ 0.01, H 2 Owt% ≤0.01), and the electrolyte used was "1 M NaClO 4 -EC / DEC (volume ratio 1:1)-FEC (5wt%)", the amount of electrolyte used is 100μL.
[0086] Example 2
[0087] Compared with Example 1, the present embodiment is different in that: in the preparation process of sodium ferrous sulfate positive electrode material for sodium ion battery; the carbon source includes graphene and acetylene black, and the weight ratio of the two is 1:1; the other conditions and steps are the same.
[0088] Example 3
[0089] Compared with Example 1, the present embodiment is different in that: in the preparation process of sodium ferrous sulfate positive electrode material for sodium ion battery, the carbon source includes graphene and CNTs-N, and the weight ratio of the two is 1:1. Other conditions and steps are the same. Among them, the preparation method of CNTs-N is as follows:
[0090] Step 1: Preparation of oxidized carbon nanotubes
[0091] Add 0.5 mol / L H 2 SO 4 After ultrasonic treatment for 30 min, CNTs / H 2 SO 4 Mixed solution; CNTs and H 2 SO 4The mass volume ratio is: 1g:200mL.
[0092] KMnO 4 Dissolved in 0.5 mol / L H 2 SO 4 In the experiment, KMnO was obtained. 4 / H 2 SO 4 Mixed solution, in which KMnO 4 With H 2 SO 4 The mass volume ratio is: 2.5g:200mL.
[0093] At 150℃, KMnO 4 / H 2 SO 4 The mixture was slowly added with CNTs / H 2 SO 4 The mixture was refluxed for 5 h, cooled to room temperature, filtered to obtain a filter cake, and the filter cake was added to 30 mL of concentrated HCl, mixed and allowed to stand for a period of time to remove the MnO generated in the reaction. 2 The mixture was then filtered and washed with water until the filtrate was neutral. The filter cake was vacuum dried at 80°C for 12 h to obtain oxidized carbon nanotubes.
[0094] Step 2: Preparation of CNTs-N
[0095] According to the weight ratio of 1:15, a mixed nitrogen source is added to the oxidized carbon nanotubes obtained in step 1, wherein the mixed nitrogen source includes methotrexate and 2-aminopyrimidine, and the weight ratio of the two is 1:4. The above mixture is ground for 30 minutes, and the obtained mixture is placed in a tube furnace, and the temperature is set to 750°C at a heating rate of 5°C / min under a nitrogen atmosphere, and the temperature is maintained for 1 hour. Then the temperature is cooled to room temperature to obtain CNTs-N.
[0096] See also Figure 5 and Figure 6 This is a TEM image of the obtained CNTs-N. Different from the hollow structure of CNTs, the obtained CNTs-N is a randomly arranged tubular structure with a length of about tens of microns, a diameter of about 50-400nm, and a wall thickness of 10-20nm. The tubular structure of CNTs-N presents a bamboo-like structure with partitions, and its bamboo-like structure is arranged more evenly. This may be because the use of a mixed nitrogen source causes the sintered carbon nanotubes to be doped with nitrogen. Nitrogen plays a key role in the formation of the bamboo-like morphology. Nitrogen absorbs the catalyst on the surface during the synthesis of CNTs-N, inhibits the surface diffusion of carbon, and promotes the volume diffusion of carbon. Nitrogen can also adjust the electronic properties of carbon atoms and increase the synthesis rate of CNTs-N.
[0097] Example 4
[0098] The present embodiment is different from the embodiment 3 in that: in the preparation process of the modified carbon nanotubes, the weight ratio of methotrexate and 2-aminopyrimidine in the mixed nitrogen source in step 2 is 1:8. The other conditions and steps are the same.
[0099] Example 5
[0100] The difference between this embodiment and embodiment 3 is that in the preparation process of modified carbon nanotubes, the weight ratio of methotrexate and 2-aminopyrimidine in the mixed nitrogen source in step 2 is 1:12. Other conditions and steps are the same.
[0101] Example 6
[0102] Compared with Example 3, the difference between this embodiment and Example 3 is that: in the preparation process of modified carbon nanotubes, after the mixed nitrogen source is mixed with the oxidized carbon nanotubes obtained in step 1 in step 2, it is mixed with the mixed sulfur source. The mixed sulfur source is cystine and 4-azidophenyl disulfide, and the weight ratio of the two is 1:1; the weight ratio of the mixed sulfur source to the oxidized carbon nanotubes is 1:10. Other conditions and steps are the same.
[0103] Example 7
[0104] Compared with Example 3, the present embodiment is different in that: in the preparation process of modified carbon nanotubes, after the mixed nitrogen source is mixed with the oxidized carbon nanotubes obtained in step 1 in step 2, it is mixed with the mixed sulfur source. The mixed sulfur source is cystine and 4-azidophenyl disulfide, and the weight ratio of the two is 1:1; the weight ratio of the mixed sulfur source to the oxidized carbon nanotubes is 1:15. Other conditions and steps are the same.
[0105] Example 8
[0106] The present embodiment is different from the embodiment 1 in that when preparing the positive electrode sheet, the positive electrode material obtained in the embodiment 1 exposed to the air for 5 days, 7 days, 14 days, 21 days and 30 days is used respectively; the other conditions and steps are the same.
[0107] Example 9
[0108] The present embodiment is different from the embodiment 3 in that: when preparing the positive electrode sheet, the positive electrode material obtained in the embodiment 1 exposed to the air for 5 days, 7 days, 14 days, 21 days and 30 days is used respectively; the other conditions and steps are the same.
[0109] Comparative Example 1
[0110] The present embodiment is different from the embodiment 3 in that in the preparation process of the sodium ferrous sulfate positive electrode material for sodium ion batteries, the carbon source includes the oxidized carbon nanotubes prepared in the embodiment 3 and graphene, and the weight ratio of the two is 1:1. The other conditions and steps are the same.
[0111] Comparative Example 2
[0112] Compared with Example 3, the present embodiment is different in that: in the preparation process of sodium ferrous sulfate positive electrode material for sodium ion battery, the carbon source includes CNTs-N and graphene, and the weight ratio of the two is 1:1; wherein, in the preparation process of CNTs-N, 2-aminopyrimidine is used instead of methotrexate. The other conditions and steps are the same.
[0113] Comparative Example 3
[0114] Compared with Example 3, the present embodiment is different in that: in the preparation process of sodium ferrous sulfate positive electrode material for sodium ion battery, the carbon source includes CNTs-N and graphene, and the weight ratio of the two is 1:1; wherein, in the preparation process of CNTs-N, methotrexate is used instead of 2-aminopyrimidine. The other conditions and steps are the same.
[0115] Test example
[0116] Electrochemical performance test
[0117] Battery tests were performed on the batteries prepared in Examples 1-9 and Comparative Examples 1-3.
[0118] The constant current charge-discharge test and cycle life test of the battery were carried out by Xinwei CT4000, and the voltage and electrochemical impedance test of the cyclic voltammetry test were carried out by Chenhua CHI760D electrochemical workstation. The test voltage window was 2.0-4.5 V, and the current density was 1 C=100 mA g -1 The charge and discharge curves of the battery obtained in Example 1 at different current densities are shown in Figure 4 The rate performance test results of the batteries obtained by using the positive electrode materials exposed to the air for different days in Examples 1 and 8 of the present invention are shown in Table 1.
[0119] Combined with Figure 1-4In Example 1 and Example 2, by adjusting the molar ratio between sulfates, a sodium ferrous sulfate positive electrode material with no impurities and high capacity was obtained according to a molar ratio of anhydrous ferrous sulfate to sodium sulfate of 1:1; according to the method of Example 1, a conductive carbon source and an aluminum source were added in the ball milling stage before the synthesis of sodium ferrous sulfate. Unlike other technologies that add conductive agents during coating, the advance addition of carbon source and aluminum source makes the precursor more evenly dispersed. After the precursor is calcined, the sodium ferrous sulfate positive electrode is evenly coated in situ by the carbon source and the alumina film, which improves the crystallinity of the sodium ferrous sulfate material on the one hand, and constructs a dense protective film and a three-dimensional conductive network on the other hand, thereby obtaining a sodium ferrous sulfate positive electrode material with high air stability and high conductivity, which helps to improve the fast charging performance and stability of sodium ion batteries.
[0120] In addition, in the above embodiments, by optimizing the ball milling process, it is helpful to promote uniform dispersion of the raw materials, greatly increase the contact area, and also help to improve the performance of the sodium ion battery.
[0121] Also, refer to the attached Figure 3 After the sodium ferrous sulfate cathode material obtained in Example 1 was exposed to the air for 14 days and 30 days, the obtained XRD pattern was not much different from that of the freshly prepared sodium ferrous sulfate cathode material. It can be seen that the sodium ferrous sulfate cathode material obtained in Example 1 has excellent air stability, is easy to realize industrial continuous production, and helps to further reduce production costs. In addition, the sodium ferrous sulfate cathode material prepared by this method has a simple preparation method and a pollution-free process flow, which is suitable for popularization and application.
[0122] Referring to Table 1, the sodium ferrous sulfate cathode material obtained in Example 1, after being exposed to the air for 5 days, 7 days, 14 days, 21 days and 30 days respectively (see Example 8), the prepared battery and the battery obtained from the freshly prepared sodium ferrous sulfate cathode material, are cycled 0-100 times at constant current and constant voltage at different current densities. See Table 1 for some test results of the reversible capacity. It can be seen from the data in Table 1 that when the number of cycles is the same, the length of time the cathode material is exposed to the air has little difference in the rate performance of the obtained battery. It can be seen that the sodium ferrous sulfate cathode material obtained in this case has excellent air stability, and the length of time exposed to the air has little effect on the performance of the obtained sodium ion battery.
[0123] Table 1 Reversible capacity of the batteries obtained in Example 1 and Example 8 (mAh g -1 ) Test Results
[0124]
[0125] In addition, for the batteries prepared in Examples 1-7 and Comparative Examples 1-3, the first charge and discharge capacity was tested at a rate of 50C and the first coulombic efficiency was calculated. The results of the first coulombic efficiency test are shown in Table 2.
[0126] Table 2 The first coulombic efficiency test results of each embodiment and comparative example
[0127]
[0128] Referring to the data in Table 2, and referring to the data of Example 1 and Example 2, it can be seen that the use of graphene, CNTs as carbon sources or the use of graphene and acetylene black as carbon sources has little difference in the effect on the first coulombic efficiency of the sodium ion battery. Referring to the data of Examples 1, 2 and Example 3, it can be seen that the use of graphene and CNTs-N as carbon sources can significantly improve the first coulombic efficiency of the sodium ion battery.
[0129] Furthermore, by comparing the data of Example 1 and Examples 3-5, it can be seen that, relative to graphene and CNTs, the addition of CNTs-N to the carbon source can significantly increase the first coulombic efficiency of the sodium ion battery by an average of 5.65%, indicating that CNTs-N has a significant effect on improving the first coulombic efficiency of the sodium ion battery; and Example 3 is better than Example 4 which is better than Example 5. It can be seen that when preparing CNTs-N, the proportion of methotrexate in the mixed nitrogen source used is increased, and the improvement effect on the first coulombic efficiency of the sodium ion battery is enhanced.
[0130] Referring to the data of Example 3 and Examples 6 and 7 in Table 2, the first coulombic efficiency of Example 7 is better than that of Example 6 and Example 3, indicating that the addition of cystine and 4-azidophenyl disulfide can further optimize the improvement effect of CNTs-N on the first coulombic efficiency, and the amount of cystine and 4-azidophenyl disulfide may be positively correlated with the first coulombic efficiency of the sodium ion battery within a certain range.
[0131] Referring to the data of Example 1, Example 3 and Comparative Examples 1-3 in Table 2, the first coulombic efficiency of Example 3 is better than that of Comparative Example 3, which is better than that of Comparative Example 2, which is better than that of Comparative Example 1, which is better than that of Example 1. It can be seen that the addition of modified carbon nanotubes can significantly improve the first coulombic efficiency of the sodium ion battery, and the effect of CNTs-N is better than that of oxidized carbon nanotubes; and methotrexate and 2-aminopyrimidine are used as mixed nitrogen sources to further modify the oxidized carbon nanotubes, and the effect is better than that of methotrexate or 2-aminopyrimidine used alone.
[0132] For the batteries prepared in Examples 1-7 and Comparative Examples 1-3, the capacity of the batteries was obtained by charging to 4.0V at 0.5C constant current and constant voltage, and discharging to 1.5V at 0.5C. The weight of the battery cell was measured with a balance, and the energy density of the battery cell was calculated. The positive electrode energy density test results are shown in Table 3.
[0133] Table 3 Test results of positive electrode energy density of each embodiment and comparative example
[0134]
[0135] Referring to the data in Table 3, and referring to the data of Example 1 and Example 2, it can be seen that the use of graphene, CNTs as carbon sources or the use of graphene and acetylene black as carbon sources has little difference in the positive electrode energy density of the sodium ion battery. Referring to the data of Examples 1, 2 and Example 3, it can be seen that the use of graphene and CNTs-N as carbon sources can significantly improve the positive electrode energy density of the sodium ion battery.
[0136] Moreover, it can be seen from the data of Example 1 and Examples 3-5 that, relative to graphene and CNTs, the addition of CNTs-N to the carbon source can increase the positive electrode energy density of the sodium ion battery by an average of 11.27%; it indicates that the use of CNTs-N in the positive electrode material of the sodium ion battery can significantly improve the positive electrode energy density; and Example 3 is better than Example 4 and Example 5. It can be seen that when preparing CNTs-N, the proportion of methotrexate in the mixed nitrogen source used is increased, and the improvement effect on the positive electrode energy density of the sodium ion battery is enhanced. It not only makes up for the positive electrode active sodium ions consumed in the first week of film formation, but also helps sodium ion transport, thereby improving the cycle stability of the battery. This may be because CNTs-N contains related groups of methotrexate and / or 2-aminopyrimidine, which makes the structure of the positive electrode sheet more stable and can maintain mechanical integrity, and can improve the structural uniformity of the positive electrode slurry in the process of preparing the sodium ion positive electrode sheet.
[0137] Referring to the data of Example 3 and Examples 6 and 7 in Table 3, the positive electrode energy density of Example 7 is better than that of Example 6 and Example 3, indicating that the addition of cystine and 4-azidophenyl disulfide can further optimize the improvement of CNTs-N on the positive electrode energy density, and the amount of cystine and 4-azidophenyl disulfide may be positively correlated with the positive electrode energy density of the sodium ion battery within a certain range. This may be because the presence of SS bonds in cystine and 4-azidophenyl disulfide further changes the spatial structure of CNTs-N, and it may also be because the SS bonds in the mixed sulfur source react with the related groups of methotrexate and / or 2-aminopyrimidine in CNTs-N to not only provide sodium embedding sites but also help promote the diffusion of sodium ions in the electrolyte.
[0138] Referring to the data of Example 1, Example 3 and Comparative Examples 1-3 in Table 3, the positive electrode energy density of Example 3 is better than that of Comparative Example 3, which is better than that of Comparative Example 2, which is better than that of Comparative Example 1, which is better than that of Example 1. It can be seen that the addition of modified carbon nanotubes can significantly improve the positive electrode energy density of sodium ion batteries; and the effect of CNTs-N is better than that of oxidized carbon nanotubes; and methotrexate and 2-aminopyrimidine are used as mixed nitrogen sources to further modify the oxidized carbon nanotubes, and the effect is better than that of methotrexate or 2-aminopyrimidine alone. This may be because after the use of methotrexate and 2-aminopyrimidine in combination, the spatial structure of the obtained CNTs-N is more complex, and the paths of sodium ions in the process of embedding and embedding are diversified, which helps to promote the diffusion of sodium ions in the electrolyte.
[0139] The conventional operations in the operating steps of the present invention are well known to those skilled in the art and will not be described in detail here.
[0140] The above-described embodiments provide a detailed description of the technical solution of the present invention. It should be understood that the above-described embodiments are only specific embodiments of the present invention and are not intended to limit the present invention. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.
Claims
1. A method for preparing a sodium ferrous sulfate positive electrode material for a sodium ion battery, comprising: Anhydrous ferrous sulfate, sodium sulfate, a carbon source and an aluminum source are mixed and ground to obtain a precursor material; The precursor material is heated and annealed under the protection of an inert gas to obtain a sintered product; The sintered product is cooled to room temperature and ground to obtain a sodium ferrous sulfate positive electrode material; the carbon source includes graphene and modified carbon nanotubes; The modified carbon nanotubes contain nitrogen, and the nitrogen comes from methotrexate and / or 2-aminopyrimidine; The modified carbon nanotubes are prepared by reacting a mixed nitrogen source with an oxidized carbon nanotube; the mixed nitrogen source includes methotrexate and 2-aminopyrimidine; the oxidized carbon nanotubes are obtained by oxidation of carbon nanotubes; in the preparation of the modified carbon nanotubes, the weight ratio of the oxidized carbon nanotubes to the mixed nitrogen source is 1:10-20; in the mixed nitrogen source, the weight ratio of methotrexate to 2-aminopyrimidine is 1:4-12; in the preparation of the modified carbon nanotubes, the mixed nitrogen source is mixed with the oxidized carbon nanotubes and then mixed with a sulfur source; the weight ratio of the sulfur source to the oxidized carbon nanotubes is 1:10-18; The aluminum source includes one or more of aluminum isopropoxide, aluminum oxide, aluminum acetate, aluminum chloride, aluminum sulfate, aluminum nitrate, aluminum oxalate and aluminum acetate.
2. The method for preparing the sodium ferrous sulfate positive electrode material according to claim 1, characterized in that: The molar ratio of anhydrous ferrous sulfate to sodium sulfate is 1-2:1; The amount of carbon source is 1-5wt% of the sum of anhydrous ferrous sulfate and sodium sulfate; the amount of aluminum source is 1-5wt% of the sum of anhydrous ferrous sulfate and sodium sulfate.
3. A sodium ferrous sulfate positive electrode material prepared by the method according to any one of claims 1-2.
4. A positive electrode sheet for a sodium ion battery, comprising a positive electrode current collector and a positive electrode film layer arranged on at least one surface of the positive electrode current collector, wherein the positive electrode film layer is coated with the sodium ferrous sulfate positive electrode material according to claim 3.
5. A sodium ion battery, comprising the sodium ion battery positive electrode sheet according to claim 4.
6. A vehicle comprising the sodium ion battery according to claim 5.
Citation Information
Patent Citations
Micron-sized porous sodium ferrous sulfate / carbon composite positive electrode material and sodium ion battery or sodium battery prepared from same
CN114050246A
Sodium ion battery
CN116404144A
Element-doped dual-carbon modified sodium ferrous sulfate positive electrode material and preparation method and application thereof
CN118099392A